Amautas’ Tinkuy - Kapsoli Escudero, Wilfredo (2018)
The objective of this essay is to explain the causes, process and consequences of the Peasant Revolution led by Pedro Pablo Atusparia and Pedro Cochachin in 1885 against the indigenous tribute known as “The Republic” by which arbitrary free jobs were demanded to be performed by the members of the local communities. During the evolution, the political project of restoring the Tahuantinsuyo and creating the new Ancash region was expanded. The revolution did not prosper and its leaders were executed by firearm or poisoned to die tragically, immolating themselves as the most emblematic popular heroes of the 19th century. A series of paintings and images illustrate those events in our social history, making that tragedy more understandable wjich substantially affected the most excluded sectors of our society.